Online Teacher and On-Site Facilitator Perceptions of Parental Engagement at a Supplemental Virtual High School - Borup, Jered; Chambers, Chawanna B.; Stimson, Rebecca (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Just as they have in face-to-face courses, parents will likely play an important role in lowering online student attrition rates, but more research is needed that identifies ways parents can engage in their students’ online learning. In this research we surveyed and interviewed 12 online teachers and 12 on-site facilitators regarding their experiences and perceptions of parental engagement. Guided by the Adolescent Community of Engagement framework, our analysis found that teachers and facilitators valued parents’ engagement when parents advised students on course enrollments, nurtured relationships and communication with and between students, monitored student progress, motivated students to engage in learning activities, organized and managed students’ learning time at home, and instructed students regarding study strategies and course content when able. Teachers and facilitators also identified obstacles that parents faced when attempting to engage in their children’s online learning as well as obstacles that teachers and facilitators encountered when they attempted to support parents.